Pengenalan Reksadana Syariah Melalui Platform Investasi Digital di Desa Logas Kecamatan Singingi - Putri Asrina; Selly Prima Desweni; Supriani Sidabalok (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This service provides socialization about sharia mutual fund investment to the community in Logas Village, Singingi District. In this service, training is also provided on how to start investing in sharia mutual funds using a digital investment platform and how to buy and sell sharia mutual funds on the digital investment platform. The main problems experienced by partners in general are the lack of knowledge about legal investment and limited knowledge about the development of information technology that can facilitate investment. So that it becomes a factor that causes partners not to try to start investing. The implementation method used is lectures, demonstrations/practices, and discussions. The implementation of this activity was attended by 10 people consisting of 8 women and 2 men with an age range of 15-44 years. From this activity, the service team succeeded in increasing the participants' understanding of sharia mutual fund investment, how to start investing in sharia mutual funds with a digital investment platform and how to carry out sharia mutual fund buying and selling transactions. This is indicated by an increase in participant knowledge as seen from the participant questionnaire score during the pre-test, which was only 47.5%, increasing to 77.75% after the training. Although the benefits of community service are very significant for participant knowledge of sharia mutual fund investment and the use of the Bibit application. However, participants are expected to continue practicing sharia mutual fund investment, to improve their skills and provide hope for a better future through investment.